UTM’s Groundbreaking COVID-19 Tracker for Strategic Pandemic Preparedness (UTMCCTA) (International Journal of Innovative Computing, 2024)
COVID-19 (novel coronavirus disease) is one of the most lethal viruses of this decade. Infected people with mild to moderate respiratory issues might have slight side effects due to the virus. However, senior individuals and individuals with serious medical problems like cardiovascular disease, serious lung disease, diabetes, or cancer, on the other hand, are considerably more likely to develop serious illnesses. Because the virus spreads via physical touch as well as through air droplets, it's critical to maintain tracking of everyone on the UTM campus, including UTM students and employees who come into contact during working hours. As a result, the UTM COVID-19 Contact Tracing System (UTMCCTA) was developed to address this problem. UTMCCTA is an automatic system that tracks contacts and notifies them if someone on their contact list tests positive for COVID-19. This program includes two user interfaces: one is a mobile app that UTM students use to automatically scan for nearby contacts, and the other is an online website that UTM Health Authorities and administrators will utilize. UTM health officials can look up a user and change their COVID-19 status from negative to positive, and vice versa. This will immediately notify any users with whom the infected person has been in touch. Furthermore, users can actively contribute to UTM's strategic preparedness by manually entering their daily commute location. This data enhances our capacity to respond proactively. Moreover, when a user contacts another user, their contact location and time are stored in the database. This information is solely accessible to the administrator, who may evaluate it and issue a locational hotspot notice to all users enrolled in the system. This innovative approach ensures that UTM is at the forefront of pandemic preparedness and response.
Keywords: Coronavirus, contact tracing, Flutter, web, mobile